Prohibition of employment in public services as a austerity measure - content and consequences of implementation - Radovanović, Danica (Glasnik Advokatske komore Vojvodine, 2022)
At the end of 2013, the Republic of Serbia adopted amendments to the Law on Budget System, which envisage measures to ban employment in public services. The application of this measure was aimed at control, reduction of expenditures and reduction of the number of employees among users of budget funds. The application of the employment ban measure was associated with more negative but positive consequences, while the health and social care sector and the education sector suffered the most and more noticeably than other sectors. The prolongation of the validity of this measure, on several occasions, was manifested through the difficult performance of activities, as well as the reduction of the quality of services provided. Accordingly, it is justified to consider the effect of the application of the measure banning employment, it's consequences, as well as whether the autonomy of public services has really been restored by adopting a decision on its abolition.
Keywords: prohibition of employment; public service; healthcare; education